Prevalence and Risk Factors of Mental Health Problems Among Healthcare Workers During the COVID-19 Pandemic: A Systematic Review and Meta-Analysis - Hao, Qinjian; Wang, Dahai; Xie, Min; Tang, Yiguo; Dou, Yikai; Zhu, Ling; Wu, Yulu; Dai, Minhan; Wu, Hongmei; Wang, Qiang (Frontiers in Psychiatry, 2021)
Objective: The purpose of this meta-analysis was to summarize the prevalence and risk factors of mental health problems among healthcare workers during the COVID-19 pandemic. Methods: We applied an optimized search strategy across the PubMed, EMBASE, Scopus, PsycINFO, and four Chinese databases, with hand searching supplemented to identify relevant surveys. Studies were eligible for inclusion if they were published in the peer-reviewed literature and used a validated method to assess the prevalence and risk factors of mental health problems among healthcare workers during the COVID-19 pandemic. Heterogeneity was quantified using Q statistics and the I2 statistics. The potential causes of heterogeneity were investigated using subgroup analysis and meta-regression analysis. Sensitivity analysis was performed to examine the robustness of the results. Results: We pooled and analyzed data from twenty studies comprising 10,886 healthcare workers. The prevalence of depression, anxiety, insomnia, post-traumatic stress symptoms, phobia, obsessive-compulsive symptoms and somatization symptoms was 24.1%, 28.6%, 44.1%, 25.6%, 35.0%, 16.2%, and 10.7%, respectively. Female and nurses had a high prevalence of depression and anxiety. Frontline healthcare workers had a higher prevalence of anxiety and lower prevalence of depression than the second-line. Furthermore, the proportion of moderate-severe depression and anxiety is higher in the frontline. Additionally, 4 studies reported on risk factors of mental health problems. Conclusions: In this systematic review, healthcare workers have a relatively high prevalence of depression, anxiety, insomnia, post-traumatic stress symptoms, phobia, obsessive-compulsive symptoms and somatization symptoms during the COVID-19 pandemic, and should focus on the HCWs at high risk of mental problems. Mental health problems in healthcare workers should be taken seriously, and timely screening and appropriate intervention for high-risk group are highly recommended.